THE SPREAD OF ZOLTÁN KODÁLY’S MUSIC EDUCATION PRINCIPLES IN THE WORLD - ASZTALOS, Andrea (Studia Universitatis Babes-Bolyai Musica, 2023)
The purpose of this study is to summarize the essence of Zoltán Kodály’s music education philosophy and concept and to shed light on the presence of this music education concept in domestic and foreign music education in the 21st century. In the study, I present how music education based on Kodály’s principles has been adapted in the USA, Great Britain, Ireland, Scotland, Greece, Netherlands, Australia, Japan, and China and how it flourishes even in the 21st century.